Minder lokale mandatarissen in Brussel? Scenario’s en impact - Emilie van Haute; Kris Deschouwer; Thibault Gaudin; Rudi Janssens; Dimokritos Kavadias; Ann Mares; Jean-Benoit Pilet; Vivien Sierens; Aurélie Tibbaut (Brussels Studies)
The number of municipal councillors and aldermen in the Brussels-Capital Region is relatively high, and increases at each election. In the debates on the functioning of the political institutions of the Region the idea to reduce the number of local representatives is regularly raised. This contribution explores the possible implications of such a reduction. Three scenarios are examined: a reduction by 10 %, by 20 % and by 30 %. For each of these scenarios, the consequences for the ideological diversity in the municipal councils, the workload for the representatives and the aldermen, the formation of coalitions, the gender balances and the position of the Dutch speaking elected representatives are simulated. For the smaller fractions, the Dutch speaking representatives and the gender balances the effects are clearly negative.